Optimum Drug Combinations for the Sedation of Growing Boars Prior to Castration - Lehmann, Heidi S. (Animals (Basel), 2017)
SIMPLE SUMMARY: Pigs are notoriously challenging patients. They are difficult to handle so the use of predictable and safe sedation techniques is required for husbandry and surgical procedures. Various combinations of sedative and analgesic drugs have been previously investigated in this species, though the combination of midazolam and detomidine with either butorphanol or morphine has not been reported for sedation in pigs. The use of these combinations was investigated in the context of adequate sedation to allow castration of boars with the aid of local anaesthetic infiltration. The combination of midazolam, detomidine with butorphanol provided a more reliable sedation combination than that including morphine. It is proposed that this combination of drugs would be useful for sedation during painful husbandry procedures in pigs. ABSTRACT: Juvenile male pigs were sedated for castration. Eight five-month old boars were sedated twice (two weeks apart) with a combination of detomidine (0.1 mg/kg), midazolam (0.2 mg/kg) and either butorphanol (0.2 mg/kg) (Group MDB, n = 8) or morphine (0.2 mg/kg) (Group MDM, n = 8) intramuscularly. The boars were positioned in lateral recumbency and lidocaine (200 mg total) was injected into the testicle and scrotal skin. Castration of a single testicle was performed on two occasions. Sedation and reaction (to positioning and surgery) scores, pulse rate, respiratory rate, haemoglobin oxygen saturation, body temperature, arterial blood gas parameters and the times to immobility and then recovery were recorded. Atipamezole was administered if spontaneous recovery was not evident within 60 min of sedative administration. Data were compared with either a paired-sample t-test or a Wilcoxon-Signed Rank Test. There was no difference in sedation score, body temperature, respiratory rate and haemoglobin oxygen saturation between MDB and MDM. Mild hypoxaemia was noted in both groups. There was less reaction to castration after MDB. The pulse rate was higher after MDM sedation. The times to immobility and then recovery were similar. The combination of MDB provided more reliable sedation than MDM. MDB may be useful for sedation for short procedures in pigs, though oxygen supplementation is recommended to avoid hypoxaemia.